The Stroke Hyperglycemia Insulin Network Effort (SHINE) Trial Protocol: A Randomized, Blinded, Efficacy Trial of Standard vs. Intensive Hyperglycemia Management in Acute Stroke. Issue 2 (February 2014) - Bruno, Askiel; Durkalski, Valerie L.; Hall, Christiana E.; Juneja, Rattan; Barsan, William G.; Janis, Scott; Meurer, William J.; Fansler, Amy; Johnston, Karen C.
Rationale: Patients with acute ischemic stroke and hyperglycemia have worse outcomes than those without hyperglycemia. Intensive glucose control during acute stroke is feasible and can be accomplished safely but has not been fully assessed for efficacy. Aims: The Stroke Hyperglycemia Insulin Network Effort trial aims to determine the safety and efficacy of standard vs. intensive glucose control with insulin in hyperglycemic acute ischemic stroke patients. Design: This is a randomized, blinded, multicenter, phase III trial of approximately 1400 hyperglycemic patients who receive either standard sliding scale subcutaneous insulin (blood glucose range 80–179 mg/dL, 4·44–9·93 mmol/L) or continuous intravenous insulin (target blood glucose 80–130 mg/dL, 4·44–7·21 mmol/L) for up to 72 h, starting within 12 h of stroke symptom onset. The acute treatment phase is single blind (for the patients), but the final outcome assessment is double blind. The study is powered to detect a 7% absolute difference in favorable outcome at 90 days. Study outcomes: The primary outcome is a baseline severity adjusted 90-day modified Rankin Scale score, defined as 0, 0–1, or 0–2, if the baseline National Institutes of Health Stroke Scale score is 3–7, 8–14, or 15–22, respectively. The primary safety outcome is the rate of severe hypoglycemia (<40 mg/dL, <2·22 mmol/L). Discussion: This trial will provide important novel information about preferred management of acute ischemic stroke patients with hyperglycemia. It will determine the potential benefits and risks of intensive glucose control during acute stroke.